Casting the Other as an existential threat: The securitisation of sectarianism in the international relations of the Syria crisis. Issue 4 (1st October 2016) - Darwich, May; Fakhoury, Tamirace
ABSTRACT: With the outbreak of the Syrian civil war, the Sunni–Shiite divide came back to the fore in regional politics. In this context, sectarian identities have now acquired a security dimension, as actors have started framing each other as existential threats. This article aims to examine the process by which sectarian identities become security issues and sources of conflict. We claim that primordial and instrumentalist and rationalist approaches to identity cannot capture the complexities of sectarianism in Middle East international relations. Instead, we draw on securitisation theory to examine the speech acts and narratives leading to the construction of sectarianism as a security issue in the Middle East. We examine Hezbollah's and Saudi Arabia's speech acts towards the Syria crisis as revelatory cases in the securitisation of the Sunni–Shiite divide in the post-2011 order.